Influence of sports fan ethnocentrism on identification and media consumption intention: a preliminary investigation with Taiwanese baseball fans. Issue 1 (27th December 2021) - Chiu, Weisheng; Won, Doyeon
Abstract: Media consumption is one of the essential sport fan behaviours. While the level of sport fans' ethnocentrism can play a critical role in their attitude and intention towards the globalised sport contents, little is known about the linkage of sports fan ethnocentrism (SFE) to identification and media consumption. Thus, the current study aimed to investigate the relationships between SFE, identification (with the player and the team), and media consumption intention. Data from 447 Taiwanese baseball fans were analysed primarily using structural equation modelling technique. The results showed that SFE had an indirect influence on media consumption through player identification (the fan-player level). Moreover, SFE also had an indirect influence on team identification via player identification. The findings of the current study contribute to the cumulative knowledge of SFE regarding the mechanism of how it influences identification in different levels and sports fans' media consumption intention.